RE-EVALUASI SISTEM PENUNTUTAN DALAM KUHAP - Tolib Effendi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
Presecution system is one of the criminal justice system’s elements. In Indonesia, the presecution system does not clearly state whether it follows legality principle or opportunity principle. A strict regulation regarding to the presecution system influences the criminal justice system. Re-evaluation of the presecution system through the opportunity principle as stated in the Draft of Criminal Code Procedure of 2008 does not only bring impacts towards the Indonesian criminal justice system but also balance the victims position which has got less attention during these years.